HIV encephalopathy: glial activation and hippocampal neuronal apoptosis, but limited neural repair. Issue 2 (14th July 2015) - Tauber, SC; Staszewski, O; Prinz, M; Weis, J; Nolte, K; Bunkowski, S; Brück, W; Nau, R
Abstract : Objectives: HIV infection affects the central nervous system (CNS), frequently causing cognitive impairment. Hippocampal injury impedes the ability to transfer information into memory. Therefore, we aimed to examine neuronal injury and repair in the hippocampal formation in HIV encephalopathy. Methods: We compared neuropathological findings in 14 autopsy cases after death from systemic complications of HIV infection and in 15 age‐matched HIV‐negative control cases after sudden death from nonneurological causes using immunohistochemistry. Results: The density of apoptotic granule cells in the dentate gyrus was higher in HIV‐infected than in control cases ( P  = 0.048). Proliferation of neural progenitor cells in the dentate gyrus was increased in HIV infection ( P  = 0.028), whereas the density of recently generated TUC‐4 [TOAD (turned on after division)/Ulip/CRMP family 4]‐expressing neurons in this region was not significantly elevated in HIV‐infected cases ( P  = 0.13). HIV infection caused microglial activation and astrocytosis in the neocortex and hippocampal formation. Conversely, we were unable to detect more pronounced axonal injury in HIV‐infected than in control cases. Conclusions: As in other infections involving the CNS, apoptosis of hippocampal neurons accompanied by microglial activation and astrocytosis is a prominent feature of HIV encephalopathy. The regenerative potential, assessed using the density of young neurons in the hippocampal dentate gyrus, in HIV infection appears to be lower than in acute bacterial meningitis and septic encephalitis.